A luta pela hegemonia e a organização política do conjunto CFESS/CRESS - Araujo, Everton Souza de (2014)
This research is focused on the analysis of the struggle for hegemony and political organization of the Federal Council of Social Service - Set CFESS / CRESS . These analyzes are interconnected to other entities in the professional category , since the interface of themes , but without depth of study in other entities and their respective histories . The analyzes represent the political organization , the discussion of hegemony , theoretical categories linked to hegemonies and discussion of collective projects being the case , the professional and corporate . Hegemony , Professional Project and its relations with the Corporate Project , beyond the political organization and mediation of basic respect and direction are axes that guide the analysis and research of this dissertation In this debate there is a comparison of projects , and respecting the individual nature of each relationship. Analyze the political organization of this important sector of the profession that is set CFESS / CRESS means to deepen the debate on hegemony and its theoretical and ideo - political categories